2012
DOI: 10.1002/adsc.201200508
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Chiral Ruthenium(II) Phenyloxazoline Complex: Reusable and Highly Enantioselective Catalyst for Intramolecular Cyclopropanation Reactions

Abstract: The intramolecular cyclopropanation of various trans‐allylic diazoacetates and alkenyl diazoketones has been achieved with excellent enantioselectivities of up to 98% ee and in quantitative yields by using a water‐soluble ruthenium(II)/hydroxymethyl(phenyl)oxazoline catalyst in a water/ether biphasic medium. The catalyst could be reused at least five times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In 2010, we developed a novel chiral complex, Ru(II)‐phenyloxazoline (Ru(II)‐Pheox) complex, which has a unique C 1 ‐symmetric structure (Figure ). Ru(II)‐Pheox can be easily synthesized from a commercially available benzoic acid derivative, an amino alcohol and a Ru source, and effectively promotes enantioselective intermolecular and intramolecular cyclopropanations with electron‐rich olefins, as well as electron‐deficient olefins, under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, we developed a novel chiral complex, Ru(II)‐phenyloxazoline (Ru(II)‐Pheox) complex, which has a unique C 1 ‐symmetric structure (Figure ). Ru(II)‐Pheox can be easily synthesized from a commercially available benzoic acid derivative, an amino alcohol and a Ru source, and effectively promotes enantioselective intermolecular and intramolecular cyclopropanations with electron‐rich olefins, as well as electron‐deficient olefins, under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic methods to execute this transformation have been notably scarce, and limited to the use of rare and expensive metals (Rh, Ru). [30][31][32][33] Furthermore, achieving broad substrate tolerance and/or high levels of enantioselectivity using these protocols has been notoriously challenged by competing sidereactions and the occurrence of trans/cis isomerism across the amide bond of diazoacetamides. 31 Alternative methods to access chiral γ-lactams via Pd-catalyzed cyclopropane functionalization have also been reported.…”
mentioning
confidence: 99%
“…Iwasa's research group reported an interesting intramolecular cyclopropanation in water as reaction medium. 119 In fact, Ru-pheox(b) is completely water-soluble, and completely insoluble in diethyl ether. The easy separation of the ether phase, which contains the cyclopropane product, from the catalyst in the water phase allows for a very simple reuse of the catalyst at least five times without significant decrease in reactivity or enantioselectivity.…”
Section: Scheme 39 Ru-pheox-catalyzed Asymmetric Cyclopropanation Of mentioning
confidence: 99%